Cricoid Pressure: Apply—But Be Ready to Release. Issue 3 (June 2017) - Turnbull, J.; Patel, A.; Athanassoglou, V.; Pandit, J. J.
Abstract : (Abstracted from Anaesthesia, 1(9):999–1003, 2016) This editorial accompanies the article by Andruszkiewicz et al. 1 on whether cricoid pressure (CP) occludes the esophagus. The editorial sought to address 3 core questions regarding the use of the CP maneuver with the intention of preventing passive regurgitation of stomach contents from the esophagus into the laryngopharynx during anesthesia induction: (1) What is the risk of pulmonary aspiration during anesthetic induction, and does CP reduce that risk? (2) What is the anatomy involved? (3) Is CP ever harmful?